The Effect of Using Comic-based E-Module Assisted by the Flipbook Maker for Remediation of Newton’s Law Misconceptions - Widya An Nisa Mukramah; Abdul Halim; Sri Winarni; Yusrizal; Safrida; Misbahul Jannah; Agus Wahyuni (Postgraduate, University of Mataram, 2023)
Misconceptions are seen as a learning barrier because they hinder students from learning and understanding new concepts. Misconceptions about mastering physics concepts occur in Newton’s Laws. The language that is difficult to understand and errors in writing are some of the causes. To overcome those problems, this study aims to use a comic-based e-module assisted by a flipbook maker to remediate misconceptions about Newton’s Laws. The research method is a pre-experimental design, with one group for prе-tеѕt and pоѕt-tеѕt. A total of 22 samples were selected based on the purposive sampling technique. The data were collected twice during the pretest and post-test using a three-tier multiple-choice diagnostic test consisting of 20 items. The analysis of misconception remediation indicates a decrease in misconceptions from 57.01% to 20.24%, with an N-Gain score of 0.71. This implies a significant reduction of misconceptions before and after treatment. This data is also supported by the results of the Wilcoxon test analysis, that is, 0.000<0.5, which means that the use of comic-based e-module significantly affects the remediation of students’ misconceptions of Newton’s Law material. This e-module is expected to be an alternative for teachers in remediating misconceptions in learning physics.